The current state of the problem of the formation of entrepreneurial competence of future economists in the conditions of the startup ecosystem of the university - Hoshko, Roman (Educological discourse, 2025)
Entrepreneurial competence of future economists is a key component of their professional training, which combines knowledge, skills, personal qualities and values, necessary for successful business in today's dynamic environment. The article systematizes the main approaches to the definition of entrepreneurial competence: competence, functional, process, innovative, interdisciplinary and contextual. It is noted that the integrative approach allows the most effective consideration of all aspects of the development of entrepreneurial abilities and adaptation to modern conditions. The formation of entrepreneurial competence of future economists is proposed to be carried out in stages, paying attention to the development of its individual components. At the preparatory stage, the emphasis is on student motivation for entrepreneurship, at the theoretical stage - on the acquisition of basic knowledge, and at the practical stage - on the application of this knowledge in real business tasks. The creative stage promotes the development of innovative thinking, while the evaluative stage allows to adjust development trajectories. The final, implementation stage ensures the practical use of the formed competencies in the business environment. The article also highlights the main problems that affect the formation of entrepreneurial competence: lack of adapted educational programs, insufficient connection between theory and practice, limited resources, motivational barriers, low level of teacher qualifications, economic instability and lack of entrepreneurial culture. Ways to overcome these problems are proposed, in particular through the creation of university startup ecosystems. The startup ecosystem of the university is considered as an innovative environment that integrates educational, scientific and business processes, contributing to the formation and implementation of student and teaching entrepreneurial initiatives. Its components include: business incubators, accelerators, co-working zones, specialized educational programs, mentoring, financial support, innovative research and business partnerships. The work presents examples of successful startup ecosystems, such as the Massachusetts Institute of Technology (USA), the University of Tartu (Estonia), and Kyiv Polytechnic Institute (Ukraine). It is emphasized that such ecosystems are key elements of modern higher education, which ensure the development of entrepreneurial competencies, contribute to economic development and form a new generation of entrepreneurs.